AB1128 Epidemiological Comparative Analysis in a Large Cohort of Rheumatoid Arthritis Patients: Results of the Spanish IMID Consortium. (9th June 2015) - Tornero, J.; Fernández-Nebro, A.; Blanco, F.; Gonzalez-Alvaro, I.; Sanmarti, R.; Maymo, J.; Ballina, J.; Fernández-Gutierrez, B.; Olive, A.; Corominas, H.; Erra, A.; Pluma, A.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a complex disease of unknown etiology, involving both genetic and environmental factors. Objectives: The aim of this study was to analyze the more relevant epidemiological characteristics in a large cohort of patients with RA and controls in the Spanish population. Methods: A cross-sectional, comparative, multicenter study of patients with RA and hypernormal healthy subjects for IMID diseases was performed.All patients were recruited through the Immune-Mediated Inflammatory Diseases Consortium (IMIDC).The IMIDC is a network of Spanish biomedical researchers focused in the study of the molecular basis of IMID diseases.All patients included in the present study were selected from the outpatient clinics of 12 Rheumatology Departments at different Spanish university hospitals.An epidemiological questionnaire developed by experts at DNA National Bank was applied to obtain all data. Results: 2, 366 RA patients and 1, 558 healthy subjects were included.77% of RA patients and 40% of controls were female.The mean age of patients with RA was 60±13 years and controls 49±7 years.The height and weight of controls was significantly higher than in patients with RA.The level of statistical significance was decreased by introducing gender and age as covariates.In our cohort, 65% of patients with RA had no education or only primary education.Control subjects mostly had secondary or higher education.The physical exercise was significantly more frequent in controls.The gender and age affect the assessment of physical activity performed by both groups of patients.Regarding employment status, most patients with RA were housewives (43%) whereas in controls were external employers (44%).RA patients most frequently used public transportation (39%) while controls use their cars (52%).The mean consumption of tobacco, alcohol and coffee was higher in controls but the significance level decreased in multivariate analysis, confirming the influence of gender and age on these variables.The average number of children in RA patients was higher than controls, a difference that was not confirmed by including confounding factors. Conclusions: In this large comparative study we describe for the first time the general epidemiological characteristics in patients with RA and healthy subjects representative of the Spanish population.RA patients are older as compared with controls and most of them are housewives with no education or primary education.The influence of gender confirms the significance level of physical activity, alcohol consumption, smoking, coffee intake, weight, height and average number of children. Disclosure of Interest: None declared